Discourse on eschatology of religions other than Islam in selected 17th century Malay texts = Perbincangan mengenai eskatologi agama-agama selain Islam di dalam teks-teks Melayu terpilih kurun ke-17 - Abdul Jalil, Mohd. Noh; Mohd Amin, Wan Mohd Azam; Alias, Majdan (International Islamic University Malaysia, 2019)
This article analyzes the discourse on eschatology of religions other than Islam in selected 17th century Malay texts. The discourse on religions other than Islam was not common in early Malay texts. Malay scholars at that time did not discuss much about religions other than Islam. This could be due to the fact that the priority at that time was on educating the local people on Islam itself. The teachings of Islam were new to them. Among the topics that gained prominence at that time were discourses on Islamic theology (tawḥīd), Islamic jurisprudence (fiqh) and Islamic mysticism (taṣawwūf). Despite the scarcity of the discussions on religions other than Islam, it was not totally neglected. Three 17th century Malay texts namely Lubb al-Kasyf of al-Sinkilī, the Tibyān of al-Rānīrī and Hikayat Seribu Masalah were found to have elements of such discourses. The religions other than Islam discussed in these texts were the Magian, Judaism and Christianity. Analysis on these three texts shows that those other religions were included in the main discourse on the Islamic eschatological issues. The discourse on religions other than Islam in these texts is concentrating on the danger posed to the Muslims. The discourse is short and not done throughout the texts. The contents of the texts are still on Islam and its teachings. The priority of the authors at that time is not to explain about religions other than Islam in their writings but to strengthen the faiths of the Malay Muslims.